2010
DOI: 10.4161/gmcr.1.3.12761
|View full text |Cite
|
Sign up to set email alerts
|

Rapeseed species and environmental concerns related to loss of seeds of genetically modified oilseed rape in Japan

Abstract: Feral rapeseed in Japan consists of Brassica rapa, B. juncea and B. napus, mostly produced by escape from crops. Brassica rapa and B. juncea were introduced from abroad long ago as leaf and root vegetables and as an oil crop and breeders have developed various cultivars. Brassica napus was introduced in the late 1800s, mainly as an oil crop. Rapeseed production in Japan is low, and most demand is met by imports from Canada (94.4% of the 2009 trade volume). Recently, spontaneous B. napus, including genetically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…Aono et al (2006) also reported the presence of barnase and barstar genes in the progeny of some of the sampled oilseed rape plants. As no GM oilseed rape has been grown for marketing purposes in Japan (Nishizawa et al, 2010), transgene presence could be attributed to the accidental loss and spillage of imported viable GMHT oilseed rape seeds. These data indicate that seed dispersal of GMHT oilseed rape will occur wherever it is transported or cultivated, so that feral plants are likely to be present along transportation routes in all countries cultivating and/or receiving imports of viable seeds of GMHT oilseed rape and in ruderal habitats in areas where GMHT oilseed rape is commercially grown.…”
Section: It Concluded That: "In the Very Unlikely Event That Such A Hmentioning
confidence: 99%
“…Aono et al (2006) also reported the presence of barnase and barstar genes in the progeny of some of the sampled oilseed rape plants. As no GM oilseed rape has been grown for marketing purposes in Japan (Nishizawa et al, 2010), transgene presence could be attributed to the accidental loss and spillage of imported viable GMHT oilseed rape seeds. These data indicate that seed dispersal of GMHT oilseed rape will occur wherever it is transported or cultivated, so that feral plants are likely to be present along transportation routes in all countries cultivating and/or receiving imports of viable seeds of GMHT oilseed rape and in ruderal habitats in areas where GMHT oilseed rape is commercially grown.…”
Section: It Concluded That: "In the Very Unlikely Event That Such A Hmentioning
confidence: 99%
“…Aono et al (2006) also reported the presence of barnase and barstar genes in the progeny of some of the sampled oilseed rape plants. As no GM oilseed rape has been grown for marketing purposes in Japan (Nishizawa et al, 2010), transgene presence could be attributed to the accidental loss and spillage of imported viable GMHT oilseed rape seeds. These data indicate that seed dispersal of GMHT oilseed rape will occur wherever it is transported or cultivated, so that feral plants are likely to be present along transport routes in all countries cultivating and/or receiving imports of viable seeds of GMHT oilseed rape and in ruderal habitats in areas where GMHT oilseed rape is commercially grown.…”
Section: Potential For Gene Transfer 32mentioning
confidence: 99%
“…The feral plants probably originated from spillage of contaminated OSR seed from freight trains (Hecht et al, 2014;Schulze et al, 2014Schulze et al, , 2015. Spillage of GM OSR seeds along transportation routes was also confirmed in Japan where cultivation of GM OSR is also prohibited (Saji et al, 2005;Kawata et al, 2009;Nishizawa et al, 2009Nishizawa et al, , 2010Aono et al, 2011;Mizuguti et al, 2011), the United States (in North Dakota 80% of feral OSR proved to be GM: Schafer et al, 2011;Sagers et al, 2012) and Canada (Yoshimura et al, 2006;Knispel et al, 2008;Beckie and Warwick, 2010;Knispel and McLachlan, 2010). Consequently, transportation and handling activities during import of GM OSR are considered the main cause of unintended occurrence and establishment of feral GM OSR in countries without GM OSR cultivation.…”
Section: Oilseed Rape As a Model System For Seed Spillage Along Transmentioning
confidence: 88%